1997
DOI: 10.1007/bf02051200
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after treatment of malignant colonic polyps

Abstract: Treatment of patients with malignant polyps must be individualized based on evolving criteria. Patients in whom polypectomy margins are inadequate should undergo colectomy. With appropriate selection criteria, patients selected for colectomy had a five-year survival rate similar to the rate of those treated by polypectomy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 16 publications
2
40
2
5
Order By: Relevance
“…In 23 series, [14][15][16][17][18][19][20][21][22][24][25][26][27]29,[31][32][33][34][35]38,[40][41][42] clinical or endoscopic follow-up data were available, ranging from 12 to 90 (median, 60) months, and accounting for 1,535 (80.1 percent) of the included polyps. Regarding endoscopic data, polyp site was clearly specified in 17 series, accounting for 1,461 polyps.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In 23 series, [14][15][16][17][18][19][20][21][22][24][25][26][27]29,[31][32][33][34][35]38,[40][41][42] clinical or endoscopic follow-up data were available, ranging from 12 to 90 (median, 60) months, and accounting for 1,535 (80.1 percent) of the included polyps. Regarding endoscopic data, polyp site was clearly specified in 17 series, accounting for 1,461 polyps.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Polyp morphology was available in 19 series, enrolling 1,145 polyps. 1 [39][40][41][42] Finally, cancerrelated death was reported in 56 (3.6 percent) of those 1,535 patients for whom follow-up data were available, with an interval from the diagnosis ranging from 5 to 101 (median, 32) months. Death because of surgical complications, inferred from 28 studies, was reported in 8 (0.8 percent) of 951 operated patients.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 3 more Smart Citations